THE EFFECT OF SUSTAINABILITY REPORTING AND TRANSFER PRICING ON TAX AVOIDANCE WITH PROFITABILITY AS A MODERATING VARIABLE IN MULTINATIONAL COMPANIES IN INDONESIA - Ni Putu Sintya Enjelika; Putu Sri Arta Jaya Kusuma (Majapahit Journal of Islamic Finance and Management, 2026)
This study examines the effect of sustainability reporting and transfer pricing on tax avoidance, with profitability as a moderating variable in multinational companies in Indonesia. Tax avoidance is a critical issue as it potentially reduces government revenue, particularly in firms with opportunities to shift profits across jurisdictions. Sustainability reporting is expected to enhance transparency and discourage aggressive tax practices, while transfer pricing is commonly used to minimize tax burdens. This study employs a quantitative approach using secondary data from annual and sustainability reports of multinational companies listed on the Indonesia Stock Exchange during 2022–2024. A total of 43 companies were selected through purposive sampling, resulting in 108 observations after outlier treatment. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show that sustainability reporting has a negative and significant effect on tax avoidance, whereas transfer pricing has a positive and significant effect on tax avoidance. Furthermore, profitability weakens the negative effect of sustainability reporting on tax avoidance and strengthens the positive effect of transfer pricing on tax avoidance. These findings indicate that both non-financial and financial factors play an important role in influencing corporate tax behavior.